The β- radio-guided surgery: Method to estimate the minimum injectable activity from ex-vivo test. (February 2019) - Russomando, A.; Schiariti, M.; Bocci, V.; Colandrea, M.; Collamati, F.; Cremonesi, M.; Ferrari, M.E.; Ferroli, P.; Ghielmetti, F.; Ghisini, R.; Grana, C.M.; Mancini Terracciano, C.; et al.
Highlights: Test on radiomarked ex-vivo meningioma specimens confirmed feasibility of β -RGS. Personalized minimal activity to be injected can be evaluated from PET images. Effective dose is at a level of whole-body PET/CT and personnel exposure negligible. Abstract : Purpose: Radio-guided surgery with β - decays is a novel technique under investigation. One of the main advantages is its capability to detect small ( ⩽ 0.1 ml) samples after injecting the patient with low activity of radiopharmaceutical. This paper presents an experimental method to quantify this feature based on ex-vivo tests on specimens from meningioma patients. Methods: Patients were enrolled on the basis of the standard uptake value (SUV) and the tumour-to-non-tumour activity ratio (TNR) resulted from 68 Ga-DOTATOC PET exams. After injecting the patients with 93–167 MBq of 90 Y-DOTATOC, 26 samples excised during surgery were analyzed with a β - probe. The radioactivity expected on the neoplastic specimens was estimated according to the SUV found in the PET scan and the correlation with the measured counts was studied. The doses to surgeon and medical personnel were also evaluated. Results: Even injecting as low as 1.4 MBq/kg of radiotracer, tumour residuals of 0.1 ml can be detected. A negligible dose to the medical personnel was confirmed. Conclusions: Radio-guided surgery with β - decays is a feasible technique with a low radiation dose for both personnel and patient, in particular if the patient is injected with the minimum required activity. A correlation greater than 80% was observed between the measured counts and the expected activity for the lesion samples based on the individual SUV and the TNR. This makes identifiable the minimum injectable radiotracer activity for cases where 90 Y is the utilized radionuclide.